Pengaruh Profitabilitas, Struktur Aset, Likuiditas, Dan Pertumbuhan Penjualan Terhadap Struktur Modal Perusahaan Makanan Dan Minuman - Gunadhi, Gede Bagus Dwiputra; Putra, I Made Pande Dwiana (E-Jurnal Akuntansi; Vol 28 No 1 (2019), 2019)
The purpose of this research is to understand the effect of profitability, asset structure, liquidity, and sales growth on the capital structure of food and beverage companies listed on the IDX. This research was conducted at 19 food and beverage companies listed on the Indonesia Stock Exchange (IDX) in 2015-2017 by accessing the website www.idx.co.id. The sample used in this study was determined using a non probability sampling method by used purposive sampling technique, so the final sample used in this study amounted to 15 companies. The data collection method used is the nonparticipant observation method. The data analysis technique used is multiple linear regression analysis. The results of this study are that profitability and liquidity have a negative influence on the capital structure, while the asset structure and sales growth have a positive influence on capital structure . Keywords: Profitability, asset structure, liquidit,  sales growth, capital structure.